The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.31686/ijier.vol5.iss6.733
|View full text |Cite
|
Sign up to set email alerts
|

Community Knowledge, Perception and Attitude Toward Breast Cancer in Sekyere East District-Ghana

Abstract: The study was conducted to determine the knowledge level of women on breast cancer, respondents perceptions about breast cancer and the attitude of the people toward breast cancer in the Sekyere East District-Ghana. The study adopted quantitative approach by collecting data through the use of questionnaire from 97 women, who were selected through stratified and simple random sampling techniques. The study established that the respondents demonstrated their knowledge level of breast cancer in their breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Participants were taken to traditional doctors. Azumah (2017) [ 27 ] Asokore in the Sekyere East District in the Ashanti Region To examine the community knowledge, perception, and attitude toward breast cancer in Asokore in the Sekyere East District. Quantitative study 97 women.…”
Section: Resultsmentioning
confidence: 99%
“…Participants were taken to traditional doctors. Azumah (2017) [ 27 ] Asokore in the Sekyere East District in the Ashanti Region To examine the community knowledge, perception, and attitude toward breast cancer in Asokore in the Sekyere East District. Quantitative study 97 women.…”
Section: Resultsmentioning
confidence: 99%
“…Hand-search of the included study references yielded no results. In total, we included 15 studies [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. The article selection process is shown in the PRISMA ow diagram (Fig.…”
Section: Literature Searchmentioning
confidence: 99%
“…A study by Iddrisu et al and Agbokey revealed that breast cancer is a disgraceful disease, dangerous, and a fast killer [21,29]. Some people also believe that breast cancer can be cured [25,30] by herbal treatment or medicine [23] while some believe that it is not curable [25]. Some people also believed that breast cancer was contagious and transmissible and avoided sharing equipment with breast cancer survivors [29].…”
Section: Misconceptions About Breastmentioning
confidence: 99%
See 2 more Smart Citations